Information system portal - Mohd Hosni, Bin Che Malik (Universiti Malaysia Sarawak, UNIMAS, 2006)
Information System Portal (IS Portal) is designed to provide information about Information System programme in Faculty of Computer Science and Information Technology, University Malaysia Sarawak (UNIMAS). The purpose of IS Portal is to provide a platform for the people in IS programme to get together and share information. The content in IS Portal can also be shared with people outside the IS programme or UNIMAS. The target user to use the portal are the lecturers, current IS students, ex-IS students and prospective students. The portal is convenient because it is always available anytime and can be access anywhere by anyone who needs the information. The study of the IS Portal is concern with the portal usability where the portal tailored to fulfill the usability characteristics. The methodology that is applied to this project is the waterfall model which consists of planning phase, analysis phase, design phase, implementation phase and testing phase. The design of the portal is using the unified modeling language (UML). The implementation of this project is using the prototype approach where paper base storyboard is used to design the page layout. The portal is developed using open source application such Apache web server, MySQL database and PHP as the server side script. There are two types of tests that had been conducted which are functionality test and usability test. IS Portal is expected to become a popular website among IS students and lecturers as a platform for them to provide and retvieve information regarding the IS activities. The prospective students are expected to use this portal to get information regarding IS programme in Unimas.